High-fat diet during pregnancy and lactation impairs the cholinergic anti-inflammatory pathway in the liver and white adipose tissue of mouse offspring. (15th February 2016) - Payolla, Tanyara Baliani; Lemes, Simone Ferreira; de Fante, Thaís; Reginato, Andressa; Mendes da Silva, Cristiano; de Oliveira Micheletti, Thayana; Rodrigues, Hosana Gomes; Torsoni, Adriana Souza; Milanski, Marciane; Torsoni, Marcio Alberto
Abstract: Cholinergic anti-inflammatory pathway (CAP) prevents inflammatory cytokines production. The main was to evaluate the effect of maternal obesity on cholinergic pathway in the offspring. Female mice were subjected to either standard chow (SC) or high-fat diet (HFD) during pregnancy and the lactation period. After weaning, only male offspring from HFD dams (HFD-O) and from SC dams (SC-O) were fed the SC diet. Key proteins of the CAP were downregulated and serum TNF-α was elevated in the HFD-O mice. STAT3 and NF-κB activation in HFD-O mice ICV injected with nicotine (agonist) were lower than SC-O mice. Basal cholinesterase activity was upregulated in HFD-O mice in both investigated tissues. Lipopolysaccharide increased TNF-α and IL-1β expression in the liver and WAT of SC-O mice, but this effect was greater in HFD-O mice. In conclusion these changes exacerbated cytokine production in response to LPS and contributed to the reduced sensitivity of the CAP. Highlights: Maternal obesity exacerbates inflammatory response in WAT and liver of offspring. Cholinergic pathway activity is downregulated in offspring of obese dams. α7nAChR expression is downregulated in WAT and liver by maternal obesity.